Are Psychological Empowerment, Quality of Work Life, Organizational Commitment, and Job Satisfaction Necessary for Employee Performance in Manufacturing? Dual-Analysis SEM-PLS and NCA - Muhammad Zain Alfain; Vitradesie Noekent; Rama Fajar Shidiq (GLOBAL HEALTH SCIENCE GROUP, 2025)
The manufacturing sector in Indonesia serves as a strategic economic pillar, significantly contributing to national growth. With a target to account for more than 20% of the Gross Domestic Product (GDP) by 2024. this sector not only drives economic development but also absorbs a substantial portion of the workforceThis study investigates the relationships between Psychological Empowerment, Quality of Work Life, Organizational Commitment, Job Satisfaction , and Employee Performance. Data from 287 Manufacturing employees in Kendal were analyzed using Structural Equation Modeling (SEM) with SmartPLS and Necessary Condition Analysis (NCA). The results show that Psychological Empowerment and Quality of Work Life significantly influence Organizational Commitment and Job Satisfaction. Both factors are also necessary conditions for these outcomes. Organizational Commitment and Quality of Work Life significantly impact Employee Performance, but Job Satisfaction does not directly affect performance in SEM. However, NCA identifies Job Satisfaction as a necessary condition for performance, emphasizing the dual importance of sufficient and necessary thresholds in Psychological Empowerment and Quality of Work Life. The study’s originality lies in combining SEM-PLS and NCA for a comprehensive analysis and exploring these relationships in an Indonesian manufacturing context. Practical implications include prioritizing employee empowerment, supportive work environments, and competitive compensation. Limitations involve the exclusion of other variables and affecting generalizability.